(untitled) (Scientific journal of the Fergana State University, 2026)
This article addresses the urgent tasks of studying the scientific heritage of our ancestors, which serves to enhance the abilities of young people in society, creating modern educational mechanisms based on strengthening respect for national values, and revealing the cognitive, political, and ethical evolution in the spiritual culture of young people, as well as the pedagogical aspects of the objective capabilities of the individual, society, and the state. In the process of developing universal metacompetence and gaining experience, the possibilities and scientific directions of finding and testing various behavioral models in a particular field of science by the student, choosing the most suitable ones for his style, requirements, taste, and values are highlighted.